2022
DOI: 10.1063/5.0073636
|View full text |Cite
|
Sign up to set email alerts
|

Active stabilization of terrestrial magnetic field with potassium atomic magnetometer

Abstract: This paper introduces a magnetically quiet environment where the magnetic-field noise is actively suppressed using an optically pumped potassium magnetometer. In a large dynamic range of Earth’s magnetic fields, the magnetic-resonance signals of potassium are completely separated in frequency, and we experimentally demonstrate that one of them could be used to measure and compensate magnetic-field noise. The magnetic-field noise floor after stabilization is ∼100 fT/Hz under a bias field ranging from 20 to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Rosner et al reported a nonmagnetic drift optically pumped cesium magnetometer with a measured sensitivity of 35 fT at integration time of 200 s and stability below 50 fT between 70 s and 600 s. [13] Ding et al used an optically pumped potassium magnetometer to suppress the magnetic noise actively and achieved a noise floor of about 100 fT/ √ Hz under a bias field from 20 µT to 100 µT. [14] As for the OPM in the study of current noise suppression, Shen et al used an optically pumped Cs atomic magnetometer to suppress the noise of a commercial CS and reached a noise level of 600 pA/ √ Hz at 1 Hz. [10] In those studies, the magnetometers they used belonged to double resonance orientation magnetometers (DROMs).…”
Section: Introductionmentioning
confidence: 99%
“…Rosner et al reported a nonmagnetic drift optically pumped cesium magnetometer with a measured sensitivity of 35 fT at integration time of 200 s and stability below 50 fT between 70 s and 600 s. [13] Ding et al used an optically pumped potassium magnetometer to suppress the magnetic noise actively and achieved a noise floor of about 100 fT/ √ Hz under a bias field from 20 µT to 100 µT. [14] As for the OPM in the study of current noise suppression, Shen et al used an optically pumped Cs atomic magnetometer to suppress the noise of a commercial CS and reached a noise level of 600 pA/ √ Hz at 1 Hz. [10] In those studies, the magnetometers they used belonged to double resonance orientation magnetometers (DROMs).…”
Section: Introductionmentioning
confidence: 99%